Answer:
2x - 13
Step-by-step explanation:
Step 1 :
1
Simplify —
2
Equation at the end of step 1 :
1
(-4x - 2) + (— • (12x - 22))
2
Step 2 :
Pulling out like terms :
3.1 Pull out like factors :
12x - 22 = 2 • (6x - 11)
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
12x - 22 = 2 • (6x - 11)
Equation at the end of step 3 :
(-4x - 2) + (6x - 11)
Y-2x=6 => y=6+2x
Y+2x=0
(6+2x) + 2x = 0
6 + 4x = 0
4x= 6
X=6/4
X= 3/2
Y=6+2x
Y=6+2. 3/2
Y= 6 + 3
Y=9
Check: y-2x=6
9-2. 3/2 = 6
9 - 3 = 6
Answer:
354
Step-by-step explanation:
44+310=354. ejeihrbebeh
Answer: 3
Step-by-step explanation:
8-5= 3.
4-3=1
so it’s 3/1 or 3